Miasmatic Rubric: Concept and Applications - Soulis, Dimitrios (Homœopathic Links, 2018)
Background The aim of this study is to distinguish repertory rubrics where at least one miasm has a significantly higher prevalence amongst the remedies included.Methods Sankaran's 10 miasm classification has been used where each remedy belongs only to one miasm. In this study, 14,486 rubrics from Schroyens ‘synthesis’ repertory were included; each one has 11 remedies at least. Pearson's chi-square test was applied to each rubric comparing the observed distribution of remedies amongst miasms to the expected one (based on the distribution of remedies amongst the whole population of rubrics).Results Total 536 rubrics were identified to be significantly different regarding the observed count of remedies in each miasm compared with the expected one.Conclusions Some of the ‘miasmatic rubrics’ identified refer to symptoms closely related to the miasm definitions and some of them do not. The latter category can give us more insight into the concept of each miasm by associating it with symptoms not currently included in miasmatic theory.
Keywords: miasms; homeopathy; repertory